2009
DOI: 10.1111/j.1532-950x.2009.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Periarticular Tibial Fracture in a Foal with a Hybrid External Fixator

Abstract: HEF should be considered as another option for repair of proximal tibial Salter-Harris type II fractures in foals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…One of the most important advantages of external fixators is that the system allows simultaneous and aggressive treatment of fractures and infected soft tissues. 9,11,19,28,29 In our study, wound treatment was easily performed in cases of open fractures.…”
Section: Discussionmentioning
confidence: 81%
“…One of the most important advantages of external fixators is that the system allows simultaneous and aggressive treatment of fractures and infected soft tissues. 9,11,19,28,29 In our study, wound treatment was easily performed in cases of open fractures.…”
Section: Discussionmentioning
confidence: 81%
“…Another study conducted by Godoy et al (2009) assessed a hybrid external fixator to fix the periarticular tibial fracture in a foal. In the mentioned study, the authors concluded that hybrid external fixators could be considered an effective surgical method to fix proximal tibial fractures [ 9 ]. One of the most secure and effective suggested surgical treatments to fix proximal physeal fractures is the use of plates and screws [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid ESF are combinations of circular and linear skeletal fixators and has been studied in large animals because these models can provide the good biomechanical properties and resistance to stresses, thus reducing the potential risk of implant failure (De Godoy et al 2009;Singh et al 2007). In an ex vivo study of tibiae from adult buffaloes, comparing the biomechanical properties of hybrid ESF, bilateral linear external fixator and circular four-ring external fixator, it was concluded that this system was more resistant than was the bilateral linear fixator .…”
Section: Application Of Esf In Orthopedic Casesmentioning
confidence: 99%